2006
DOI: 10.1128/jvi.00776-06
|View full text |Cite
|
Sign up to set email alerts
|

The L2 Minor Capsid Protein of Low-Risk Human Papillomavirus Type 11 Interacts with Host Nuclear Import Receptors and Viral DNA

Abstract: Analysis of the interactions of low-risk human papillomavirus type 11 (HPV11) L2 with karyopherin ␤ (Kap ␤) nuclear import receptors revealed that L2 interacted with Kap ␤ 1 , Kap ␤ 2 , and Kap ␤ 3 and formed a complex with the Kap ␣ 2 ␤ 1 heterodimer. HPV11 L2 contains two nuclear localization signals (NLSs)-in the N terminus and the C terminus-that could mediate its nuclear import via a classical pathway. Each NLS was functional in vivo, and deletion of both of them abolished L2 nuclear localization. Both NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…KNβ3 also binds to and mediates nuclear transport of some viral proteins, including the L2 protein of HPV-16 and HPV-11. This interaction occurs via L2 nuclear localization signals, one in the N-terminus and one in the C-terminus [32,33]. We show that the 16E5-KNβ3 interaction primarily is mediated by 10 amino acids at the C-terminus of 16E5, since a C-terminal 16E5 (−10) deletion mutant is largely defective for binding KNβ3.…”
Section: Discussionmentioning
confidence: 92%
“…KNβ3 also binds to and mediates nuclear transport of some viral proteins, including the L2 protein of HPV-16 and HPV-11. This interaction occurs via L2 nuclear localization signals, one in the N-terminus and one in the C-terminus [32,33]. We show that the 16E5-KNβ3 interaction primarily is mediated by 10 amino acids at the C-terminus of 16E5, since a C-terminal 16E5 (−10) deletion mutant is largely defective for binding KNβ3.…”
Section: Discussionmentioning
confidence: 92%
“…L1/L2 aggregates, presumably, are the nucleation site for further capsid assembly, suggesting that L2 plays an important role in initial, regulated assembly of VLPs. Further linking the importance of L2 in native virion assembly is its ability to bind both L1 and DNA, suggesting that L2 is the mediator that facilitates assembly (Fligge et al, 2001;Fay et al, 2004;Bordeaux et al, 2006). Further, the analysis of in vitro assembly of L1/L2 VLPs has shown that L2 is incorporated into VLPs only when co-expressed with L1, or with L1 capsomeres .…”
Section: Structural Alterations Affecting Functionmentioning
confidence: 99%
“…These same experiments utilizing L2-deficient native virions depicted a role for L2 in DNA encapsidation and/or structural stability of the virions, since fewer DNase-resistant genomes were detected in the L2-deficient samples when compared with the wild-type native virions (Holmgren et al, 2005). Over the years, many publications have cited the appearance of viral and/or cellular factors that co-purify with native virions, such as E2, E4, E5, E7, and histones (Doorbar and Gallimore, 1987;Larsen et al, 1987;Heino et al, 2000;Fligge et al, 2001;Chromy et al, 2003Chromy et al, , 2006Gu et al, 2004;Bordeaux et al, 2006;Richards et al, 2006;Kondo et al, 2007;Bird et al, 2008;Buck et al, 2008).…”
Section: Structural Alterations Affecting Functionmentioning
confidence: 99%
See 2 more Smart Citations